Leveraging cognitive consistency to nudge conservative climate change beliefs. (February 2019) - Gehlbach, Hunter; Robinson, Carly D.; Vriesema, Christine Calderon
Abstract: People feel motivated to maintain consistency across many domains in life. When it comes to climate change, many find themselves motivated to maintain consistency with others, e.g., by doubting climate change to cohere with friends' and neighbors' beliefs. The resulting climate skepticism has derailed discussions to address the issue collectively in the United States. To counteract these social consistency pressures, we developed a cognitive consistency intervention for climate skeptics. We first demonstrated that most people share substantial faith in a variety of scientific findings, across disciplines ranging from medicine to astronomy. Next, we showed that conservative participants who first acknowledged several general contributions of science subsequently reported significantly stronger beliefs in climate science (as compared to conservatives who were asked only about their climate science beliefs). These findings provide an encouraging proof-of-concept for how an inclusive climate conversation might be initiated across the political divide. Highlights: Conservatives and Liberals share a common belief in science. Conservatives believe in climate science more after reporting that they believe in science. Participants' level of egalitarianism does not moderate this treatment effect. A common belief in science may provide a promising starting point for climate conversations.